The correlation of placental histopathology with neonatal outcome - Dr Sunil Kumar; Dr. Vijaya Sudarshan (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Placenta is a vital organ for the wellbeing of the fetus. Neonatal morbidity and mortality may have its root in the placenta which can be studied from its pathological examination. Objective: This study was designed to explore the correlation of placental histopathology with neonatal outcome.Methods: The study was conducted at the Department of Obstetrics and Gynecology Pediatrics, Raipur. In the study, 100 placentas (with their membrane and cords) were included, among which 76 placentas belonging to neonates with different morbidities like preterm delivery, birth asphyxia, IUGR, septicemia were studied for histopathological changes.Results: Preterm neonates were found to have more infective and inflammatory lesions in the form of chorioamnionitis (33%). In our study, a higher incidence of villitis was found in IUGR neonates (17.4% of cases). Stillborn neonates had a high incidence of chorioamnionitis (40% vs. 16%), funisitis (40% vs. 8%) and villitis (40% vs. 8%) in their placenta. Significant changes were found in the placentas of the neonates who expired in their neonatal period. Placentas in low birth weight babies were found to have marginally higher chorioamnionitis (22% vs. 16%), increased villitis (22% vs. 8%), syncytial knotting (37% vs. 16%), and cytotrophoblast proliferation (22% vs. 8%).Conclusion:The inflammatory lesions were found to be highly prevalent in the stillborn highlighting a significant role of the infection in the causation of preterm delivery and subsequently in neonatal morbidity and mortality. So, placental pathological analysis is very important to predict the risk of developing serious inflammatory complications in neonates.